Investigation of transfer of naturalization of athletes in the Olympic Games according to sport sciences students - Sahin, S.; Dal, S. (European Journal of Physical Education and Sport Science, 2019)
In today's globalizing world, unlike others, only a few countries and industries have remained or have opted out of globalization. Globalization shows its effects in sports. The desire of the countries to be more successful in international sports competitions, making athletes of different nationalities their citizens and entering them to the competitions constituted the concept of naturalization of athletes. Whether the successes of the naturalized athletes are ethical or whether these athletes prevent the development of domestic athletes is constantly on the agenda. From this point of view, our research focuses on the perspectives of university students studying in sports sciences to naturalization of athletes. Total of 891 participants voluntarily participated in the study. The Cronbach's Alpha value of the scale, which was used to find out the opinions of the participants about transfer of allegiance of athletes, was found 0,79. Percentage, frequency, t-test and Anova test were used to evaluate the scale. As a result the participants say that; in the future sports infrastructure development must be support instead of naturalization of athletes and their transfer fee should be used for investment in national athletes` development. Successes of the naturalization of athletes are the loss of prestige for Turkey. In order to prevent this, sports infrastructure based education programs can be given more importance.